Pengaruh Penerapan Sistem E-Filing, Pemahaman Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak - Sunarto Sunarto; Yuyuk Liana (JIATAX (Journal of Islamic Accounting and Tax), 2020)
The purpose of this study was to determine the effect of applying the E-Filing system to Taxpayer Compliance. The population in this study is the small business unit in Batu District. The research sample is 80 taxpayers. the sampling method uses simple random sampling, the data analysis technique is using regression. The results showed that the first hypothesis namely the adoption of the E-Filling system against Taxpayer Compliance was accepted, In the second hypothesis Understanding Taxation of Taxpayer Compliance was accepted and the third hypothesis there was a significant effect of taxation sanctions on tax compliance.